Congruence in advertising, how can communication deal with cultural diversity? The case of HSBC campaign - Georges AOUN; Joseph Luis DEL OLMO; Stephane BOURLIATAUX-LAJOINIE (Proche-Orient Études en management, 2019)
Mass marketing which prevailed in the 20th Century is fading and is quicklybeing replaced by customized marketing as consumers are becoming moresophisticated and are now actively looking for companies that can satisfy theirspecific needs. It is clear that marketers in the 21st Century face many challenges:longer life expectancy and the increase in the number of seniors within thepopulation, fast-paced development of technologies applied to communicationand marketing, globalization which has led to the free movement of people,goods and services, the emergence of cultural factors in many markets. Atthe same time, these challenges provide new opportunities for marketers andgenerate certain impacts and influences on the whole field of marketing.